Enzymatic Conversion of Flavonoids using Bacterial Chalcone Isomerase and Enoate Reductase1. Issue 5 (20th December 2013) - Gall, Mechthild; Thomsen, Maren; Peters, Christin; Pavlidis, Ioannis V.; Jonczyk, Patrick; Grünert, Philipp P.; Beutel, Sascha; Scheper, Thomas; Gross, Egon; Backes, Michael; Geißler, Torsten; Ley, Jakob P.; et al.
Abstract Flavonoids are a large group of plant secondary metabolites with a variety of biological properties and are therefore of interest to many scientists, as they can lead to industrially interesting intermediates. The anaerobic gut bacterium Eubacterium ramulus can catabolize flavonoids, but until now, the pathway has not been experimentally confirmed. In the present work, a chalcone isomerase (CHI) and an enoate reductase (ERED) could be identified through whole genome sequencing and gene motif search. These two enzymes were successfully cloned and expressed in Escherichia coli in their active form, even under aerobic conditions. The catabolic pathway of E. ramulus was confirmed by biotransformations of flavanones into dihydrochalcones. The engineered E. coli strain that expresses both enzymes was used for the conversion of several flavanones, underlining the applicability of this biocatalytic cascade reaction.